2017
DOI: 10.1016/j.actamat.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

High temperature stress and its influence on surface rumpling in NiCoCrAlY bond coat

Abstract: The objective of this work is to develop a methodology to measure the high temperature stress in the bond coat, and investigate its role on the surface rumpling. We first presented an analytical model to evaluate the high temperature stress using X-ray sin 2 Ψ technique coupling with the curvature measurement at room temperature. A typical NiCoCrAlY bond coat with a Hastelloy-X substrate was employed as a model sample. During exposure at 1150 ºC , the bond coat was under tension at high temperature, increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Rumpling was also reported in MCrAlY coating [36][37][38]. The increased strength of bond coat can reduce the incidence of rumpling.…”
Section: Strengthening Bond Coats By Hard Phasesmentioning
confidence: 86%
“…Rumpling was also reported in MCrAlY coating [36][37][38]. The increased strength of bond coat can reduce the incidence of rumpling.…”
Section: Strengthening Bond Coats By Hard Phasesmentioning
confidence: 86%
“…It has been widely used in the testing and characterization of stress among TBCs. XRD has been used to study the stress evolution in the ceramic top coat and bond coat after operating at different conditions [33][34][35]. Meanwhile, Xiao et al studied the stress evolution of the bond coat during oxidation at 1150°C for different time based on XRD.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…It was found that the stress in the bond coat mainly generated during the process of cooling from 1150 to 600°C. This may be due to that the β phase deposition during cooling changes the volume of the bond coat [34,35].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…Although, the application of MCrAlY coatings usually requires a much thicker thickness in industrial application, where the rumpling is less significant, to understand stress evolution in coating still helps to explain the TGO spallation. Yang et al [112] developed a new approach to investigate the coating high temperature stress, results showed that the volume shrinkage of β-γ phase transformation is responsible for the stress build-up in coating, and the grain sliding in response to the high temperature stress in coating is the dominant factor for the surface rumpling.…”
Section: Residual Stress In Coatingmentioning
confidence: 99%